ANALYSIS OF TYPES OF ASSIGNMENTS THAT DEVELOP READING COMPREHENSION SKILLS (World Bulletin of Social Sciences, 2024)
In schoolchildren, the passivity of the “understanding” skill in the process of reading the text negatively affects their future activity. Therefore, the development of this skill is the goal of today's native language education process. The implementation of this work is carried out through the effective use of types of assignment that stimulate various cognitive activities during classes. The study was conducted on 9th graders (ages 14-15) of general secondary schools. Pedagogical experiment, testing and other methods were used in the coverage of the topic. For experimental lessons, interesting texts of different styles were selected, on which cognitive tasks were developed. According to the results, with the help of these lessons, the understanding skills of students increased by 14% on average.